1985
DOI: 10.1128/aac.27.4.574
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity of BMY-28142, a new extended-spectrum cephalosporin

Abstract: The In vitro activity of BMY-28142 was compared with that of cefotaxime, ceftazidime, moxalactam, and imipenem against 639 clinical isolates and a number of in vitro-selected resistant mutants. BMY-28142 was the most potent compound against the members of the family Enterobacteriaceae with a MIC for 90% of the strains of 0.12 ,ug/ml. The activity against Pseudomonas aeruginosa was comparable to that of ceftazidime and imipenem. Strains of staphylococci were moderately susceptible to BMY-28142 (MIC required to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
2

Year Published

1986
1986
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…1). It is very active against Staphylococcus aureus and Pseudomonas aeruginosa and more potent than other new broadspectrum ,B-lactam antibiotics against some members of the Enterobacteriaceae family (3,6,11). BMY-28142 is also very effective against many P-lactamase-producing strains.…”
mentioning
confidence: 99%
“…1). It is very active against Staphylococcus aureus and Pseudomonas aeruginosa and more potent than other new broadspectrum ,B-lactam antibiotics against some members of the Enterobacteriaceae family (3,6,11). BMY-28142 is also very effective against many P-lactamase-producing strains.…”
mentioning
confidence: 99%
“…In vitro studies performed prior to the commercial availability of cefepime showed that the MIC 90 ranged from 0.06 to 0.5 g/ml (12,25,26). In contrast, an assessment of isolates from North American intensive care units in 2003 showed that the MIC 90 was 2 g/ml, with MICs of some isolates as high as Ͼ16 g/ml (20).…”
mentioning
confidence: 99%
“…Against members of the family Enterobacteriaceae, MICs for 90% of strains are generally <0.5 mg/liter, against Pseudomonas aeruginosa they are <8 mg/liter, and against Staphylococcus aureus they are <4 mg/liter (6,15,16). In healthy adult volunteers, cefepime exhibited a multicompartmental serum concentration-versus-time profile with an elimination half-life (t12,3) of approximately 2 h (14).…”
mentioning
confidence: 99%
“…Against members of the family Enterobacteriaceae, MICs for 90% of strains are generally <0.5 mg/liter, against Pseudomonas aeruginosa they are <8 mg/liter, and against Staphylococcus aureus they are <4 mg/liter (6,15,16 While those investigations involved noninfected volunteers who were evaluated following single-dose administra-tion, the ultimate recipients of an intravenous antibiotic are hospitalized patients who receive maintenance-dose therapy for the treatment of infections. Pharmacokinetic parameters derived from single-dose studies, however, do not always accurately predict multiple-dose disposition (8).…”
mentioning
confidence: 99%